The Influence of Training and Work Facilities on Performance Improvement Mediated By Motivation: A Case Study at The Fire and Rescue Department of Bandung Regency - Muhammad Lutfiansyah; Nurul Hermina (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyse the effect of training and work facilities on improving performance mediated by work motivation at the Bandung Regency Fire and Rescue Service. This research is motivated by the low achievement of officer response time in meeting minimum service standards. The research method used is a quantitative approach with path analysis techniques. The population in this study amounted to 108 people, and all were sampled through the census technique. The results showed that training has a positive and significant effect on performance and work motivation. Work facilities have a significant effect on work motivation, but do not show a direct effect on improving performance. Work motivation proved to be a significant mediating variable in bridging the effect of training and work facilities on performance. These findings suggest that improving organisational performance depends not only on technical aspects, but also on psychological factors such as work motivation. Therefore, an integrated human resource development strategy is needed, including relevant training, provision of adequate work facilities, and systematic efforts to increase employee motivation.